Socio-Culture Strengthening Strategy in Character Building through the Inventorization of Minahasa Local Proverbs - Stephani Johana Sigarlaki; Isnawaty Lydia Wantasen; Maxi Kojong (Soegijapranata Catholic University, 2025)
The preservation of local culture faces significant challenges in the era of globalization, where the Fourth Industrial Revolution profoundly influences human life. Various factors contribute to the erosion of local cultures, with one of the primary factors being the diminishing interest in local issues such as languages, songs, dances, and other cultural elements. Across most Indonesian regions, the use of local languages, a vital heritage of local culture, has significantly declined. This concerning trend is evident in the Minahasan community like Tonsea. Consequently, the study of Minahasan proverbs has become a priority. This research aims to elucidate the significance of Tonsea proverbs as a socio-cultural strategy in character building. The method employed in this study is descriptive qualitative, incorporating a hermeneutic approach. The research results reveal thirty proverbs, considered oral literature, that encapsulate indigenous and invaluable values. These proverbs are deeply rooted in the Tonsea culture context, showcasing profound wisdom and values that are instrumental in character development. This study underscores the importance of preserving and promoting these proverbs as a means of preserving Tonsea's cultural heritage in the face of contemporary challenges posed by globalization and rapid technological advancements